APLIKASI MULSA DI LAHAN SAWAH TADAH HUJAN TERHADAP SERAPAN HARA NITROGEN DAN POSFOR TANAMAN KEDELAI DAN JAGUNG - Asrijal Asrijal; Ambo Upe (Journal TABARO Agriculture Science, 2017)
Experiment research will be executed farm of rice field of sample of BPP Palaguna of Regency Wajo. Obstetrical Analysis hara of crop and land;ground in Laboratory of Fertility of Land;Ground of Faperta Unhas.  This Research aim to to analyse the ability of absorption hara of crop of good maize and soy singlely with the Application Mulsa Wet ricefield dependant to rain Farm.  Research will be done/conducted by using Factorial Device in Group ( RDG). First Factor that is crop type with three treatment level that is L1 = Soy; L2 = Maize; and L3 = Maize + Soy. Second Factor that is gift mulsa   (M1) and without mulsa (M0). Each;Every attempt unit repeated by 3 times, so that there are 18 plot, added a plot which is not cultivated as control for the perception of dynamics of hara N and P without cultivation palawija. Reason of the crop election for example because both types of the crop own the system of root and different morphology characteristic is which possibility will influence the ability of conservation N.  Result of analysis indicate that ability of absorption of hara N and P of crop of good maize and soy singlely is goor with the Application Mulsa Wet ricefield dependant to rain Farm.